2006
DOI: 10.1037/0022-3514.91.4.612
|View full text |Cite
|
Sign up to set email alerts
|

See what you want to see: Motivational influences on visual perception.

Abstract: People's motivational states--their wishes and preferences--influence their processing of visual stimuli. In 5 studies, participants shown an ambiguous figure (e.g., one that could be seen either as the letter B or the number 13) tended to report seeing the interpretation that assigned them to outcomes they favored. This finding was affirmed by unobtrusive and implicit measures of perception (e.g., eye tracking, lexical decision tasks) and by experimental procedures demonstrating that participants were aware o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
433
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 568 publications
(463 citation statements)
references
References 92 publications
(92 reference statements)
27
433
2
1
Order By: Relevance
“…These authors showed that individuals with egalitarian vs. inegalitarian values diverged in their ratings of how aggressively the police treated protesters depending on whether they were that told the demonstrators were protesting in opposition to abortion or in favor of gays' entry to the military. Balcetis and Dunning (2006) showed that individuals were more likely to perceive the same ambiguous shape as a "B" when "13" was associated with an undesired outcome, but as "13" when the outcome assignments were switched, providing evidence that individuals' motivations can exert top-down influences even on individuals' visual perception.…”
Section: Evidence For Motivated Cognitionmentioning
confidence: 93%
“…These authors showed that individuals with egalitarian vs. inegalitarian values diverged in their ratings of how aggressively the police treated protesters depending on whether they were that told the demonstrators were protesting in opposition to abortion or in favor of gays' entry to the military. Balcetis and Dunning (2006) showed that individuals were more likely to perceive the same ambiguous shape as a "B" when "13" was associated with an undesired outcome, but as "13" when the outcome assignments were switched, providing evidence that individuals' motivations can exert top-down influences even on individuals' visual perception.…”
Section: Evidence For Motivated Cognitionmentioning
confidence: 93%
“…It has been shown, for example, that goal-congruent objects (e.g., palatable foods or a glass of water) are perceived as larger in size when the relevant goal (e.g., eating enjoyment or drinking) has been activated by priming (van Koningsbruggen, Stroebe, & Aarts, 2011;Veltkamp, Aarts & Running head: ROLE OF ATTENTION IN GOAL PRIMING 6 Custers, 2008). Also, it has been shown that desires can influence an individual's interpretation of ambiguous stimuli that assign the individual to a favored outcome (Balcetis & Dunning, 2006). Similarly, active goals can hinder performance on other tasks, which suggests attentional distraction from tasks that are unrelated to the goal (Masicampo & Baumeister, 2011a;Masicampo & Baumeister, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…it relates to experiences that we have made in the past. This suggests a circular organization between our past experiences and future plans, as the goals we pursue seem to organize the environment in a way that we perceive and attune to features that are helpful for us to reach these goals (Clark 2016;Balcetis and Dunning 2006;Bruner 1957;Ferguson and Bargh 2004).…”
Section: Unlearning Through the End: The Loss Of Goalmentioning
confidence: 99%